2009
DOI: 10.3844/ajidsp.2009.263.272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antioxidant Vitamins C and E Supplementation on its Plasma Levels and on Lipid Profile in Pulmonary Tuberculosis Patients26

Abstract: Problem statement: Patients with active pulmonary Tuberculosis (TB) are malnourished as indicated by reductions in lean mass, anthropometric indices and micronutrient status. Supplementation with vitamins may prove to be beneficial. Limited information is available on the supplementation of vitamin C and E in pulmonary TB patients. Hence, the present study was undertaken to address the question whether any benefit could be demonstrated with supplementation of antioxidant vitamins C and E and in combination in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
2
0
2
Order By: Relevance
“…The low antioxidant level is caused by inadequate intake and increased free radicals in the phagocytosis of Mycobacterium. These results agree with the study by Madhavi et al, (20) who found that tuberculosis patients receiving high doses of vitamin C for 2 weeks showed increased total antioxidants. These results are supported by a study in Bandung, reporting that administration of vitamin C is of benefit for increasing the antioxidant level in patients with pulmonary tuberculosis.…”
Section: Discussionsupporting
confidence: 83%
“…The low antioxidant level is caused by inadequate intake and increased free radicals in the phagocytosis of Mycobacterium. These results agree with the study by Madhavi et al, (20) who found that tuberculosis patients receiving high doses of vitamin C for 2 weeks showed increased total antioxidants. These results are supported by a study in Bandung, reporting that administration of vitamin C is of benefit for increasing the antioxidant level in patients with pulmonary tuberculosis.…”
Section: Discussionsupporting
confidence: 83%
“…These results suggest that Jordanians eat adequate animal products to increase the daily intake of vitamin B12. However, it is possible that there may be other important factors like geographical variation (Bindra et al, 1987), different life style (Papandreou et al, 2006), racial and ethnic differences (Bindra et al, 1987), genetic factors (Feng et al, 2009;Jang et al, 2002), normal absorption of vitamin B12 (Roddie and Davis, 2009), the storage period of fresh juices (Chandrasekaram et al, 2009), adequate daily intake of vitamin B12 and folic acid (Fenech, 2001), the plasma level of vitamin E and vitamin C (Adewolu and Aro, 2009;Madhavi et al, 2009) as well as the accurate cooking of vegetables (Rowe et al, 2009) and folic acid supplementation of grain products (Roddie and Davis, 2009), that were not taken in consideration in this study that could influence the vitamin B12 status of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…By its free radical quenching activity, it breaks chain propagation and thus terminates free radical attack at an early stage and the methyl groups of tocopherol interact with the cis double bounds of the fatty acids to form a stable complex in membrane phospholipids. Supplementation with vitamin E in humans decreases the susceptibility of LDL to oxidation in vivo (Madhavi et al, 2009). Some studies have shown that vitamin E has beneficial effects on plasma lipids (Park and Choi, 2002;Gazis et al, 1999;Maria, 2001;Jain and Palmer, 1996;Halliwell, 2002).…”
Section: Discussionmentioning
confidence: 99%